Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae) - Decae, Arthur; Mammola, Stefano; Rizzo, Pierluigi; Isaia, Marco (Zootaxa, 2019)
The type-genus of the mygalomorph spider family Ctenizidae (Cteniza) is newly diagnosed and described. The type-species of Cteniza (C. sauvagesi) is reestablished by describing and designating a neotype collected at the type locality of the species, in Corsica. Alongside the female neotype, the male of C. sauvagesi is redescribed, as well as both sexes of C. moggridgei. We confirm the presence of C. sauvagesi in Sardinia and record this species for the first time in mainland Italy (Calabria) and the island of Ponza (Thyrrenian Sea). Based on our findings, Cteniza sauvagesi and C. moggridgei are diagnosed on subtle differences in their morphology. Differences between the two species in ecology and distributions are also explored by means of species distribution modeling. Finally, we amend the taxonomic status of two species whose validities have long been questionable. C. brevidens is synonymized with C. sauvagesi, and C. ferghanensis is transferred to the genus Ummidia.